Islamic Colleges in Central Sumatra in The 1930s-1950s: The Beginning Efforts of Bringing between The Islamic Science and The Western Science at Local Level - Dedi Arsa (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2019)
This article discusses the discourse of Islamic Colleges in Indonesia and its realization at the local level with the establishment of Islamic Colleges in Central Sumatra, throughout the late 1930s to the 1950s.During that period, the initial discourse on Islamic Colleges in the national level went on sardonically, especially over bridging the Islamic sciences and general sciences (Western); the lingua francareferred to (Malay, Arabic, Dutch, or English); who should engender the Islamic Colleges; and who should manage them. This discourse at the national level involved prominent scholars like Satiman and Natsir, then Hatta in the following period. Their ideas were then realized in the form of the establishment of Colleges at the local level (regional), one of which was in Central Sumatra, during that period, there had been two Islamic Colleges: Sekolah Islam Tinggi (SIT) P.G.A.I in Padang in the late of colonial period and Darul Hikmah University (UDH) in Bukittinggi at the beginning of independence. Even though both of them were short-lived, they had become a prototype for Islamic Colleges in the following period as an effort to reconcile Islamic sciences and Western sciences, which is now popular as a science integration movement.Artikel ini membahas diskursus sekolah tinggi Islam di Indonesia dan realisasinya di tingkal lokal dengan didirikannya sekolah-sekolah tinggi Islam di Sumatra Tengah sepanjang 1930an akhir hingga 1950an. Selama kurun itu, diskursus awal tentang pendidikan tinggi Islam di nasional berlangsung sengit, terutama bersoal menjembatani ilmu-ilmu keislaman dan umum (kebaratan); bahasa pengantar yang diacu (Melayu, Arab, Belanda, atau Inggris); siapa yang harus melahirkan sekolah tinggi Islam; dan siapa pula yang harus mengelolanya. Diskursus ini di tingkat nasional melibatkan para cendikiawan terkemuka serupa Satiman dan Natsir, lalu Hatta dan lain-lain di masa setelahnya. Gagasan-gagasan mereka kemudian direalisasikan dalam bentuk pendirian-pendirian perguruan tinggi di tingkat lokal (daerah), salah satunya di Sumatra Tengah, di mana selama kurun itu telah berdiri berturut-turut dua sekolah tinggi Islam: Sekolah Islam Tinggi (SIT) P.G.A.I di Padang pada masa akhir kolonial dan Universitas Darul Hikmah (UDH) di Bukittinggi pada awal kemerdekaan. Sekalipun keduanya berumur singkat, tetapi telah menjadi role models bagi sekolah tinggi Islam yang ada di periode setelahnya sebagai upaya yang sama untuk mendamaikan antara ilmu-ilmu keislaman dan kebaratan, yang sekarang populer sebagai gerakan integrasi ilmu.